Children’s and adolescents’ reports on their quality of life during the COVID-19 pandemic - Borualogo, Ihsana Sabriani; Casas, Ferran (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2021)
COVID-19 affects human life, but very few studies have examined the quality of life of children and adolescents during the pandemic. This article aims to report on the quality of life of children and adolescents (N = 1,474; ages 10-18 years) during the COVID-19 pandemic in Indonesia. Data were collected using Google Forms and convenience sampling. The measuring instrument used measured five domains of quality of life, namely material, physical, social, emotional, and productive well-being. The data were analyzed using crosstab, frequency, comparison of mean values, and ANOVA. The results show that children and adolescents have been able to maintain their subjective well-being and adapt to unpleasant situations during the lockdown. Younger boys and girls show significantly higher mean scores than older ones. Children and adolescents reported that they were bored because they had limited physical activities, were dissatisfied with school closures and with what they had learnt at home, and were frustrated by the limited contact they had with friends. The research has implications in providing advice to parents, teachers, children, and adolescents to improve the quality of life of children and adolescents during the pandemic.